Social Networks Addiction (SNA-6) – Short: Validity of Measurement in Mexican Youths - Salas-Blas, Edwin; Merino-Soto, César; Pérez-Amezcua, Berenice; Toledano-Toledano, Filiberto (Frontiers in Psychology, 2022)
There is a need to respond to the excessive use of social networks, measuring this phenomenon for the purpose of evaluation, prevention and intervention of adolescents and young people. The objective of the study was to adapt and psychometrically validate the Brief Scale of Addiction to Social Networks (SNA-6), among Mexican adolescents and young adults. The participating sample consisted of 2789 students from 6 public educational campuses in Cuernavaca (Morelos, Mexico). Data collection was carried out through a web platform, strictly maintaining anonymity, voluntary participation and confidentiality. Data analysis first focused on the detection of possible response biases (random intercept model, and careless / insufficient effort), the quality of the response structure (partial credit model), dimensionality (CFA and invariance), and the relationship with external variables. It was found that the range of efficient response options can be less than five, reliability is high (.91), unidimensionality was maintained, and response biases slightly affected the dimensional structure of the instrument. Measurement invariance reached up to scalar invariance in the sex, age, and campus groups. The association with sensation seeking and depression, controlling for sex and age covariates, were statistically significant, small, and theoretically consistent. Implications of the results are discussed.